2020
DOI: 10.3390/pr8070838
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of Workshop Scheduling with Multiprocess Route Considering Logistics Intensity

Abstract: In order to solve the problems of flexible process route and workshop scheduling scheme changes frequently in the multi-variety small batch production mode, a multiprocess route scheduling optimization model with carbon emissions and cost as the multi-objective was established. At the same time, it is considered to optimize under the existing machine tool conditions in the workshop, then the theory of logistics intensity between equipment is introduced into the model. By designing efficient constraints to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hakeem-Ur-Rehman et al [33] studied multilevel and multistage batch and scheduling demand information updating problems with the objective of minimizing the total production and inventory costs and established a mixed integer programming (MIP) model. To solve the problem of flexible process routes and frequent changes in workshop scheduling schemes in multiple varieties and small batch production modes, Sun et al [34] established a multi-process route scheduling optimization model with carbon emissions and cost as multiple objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hakeem-Ur-Rehman et al [33] studied multilevel and multistage batch and scheduling demand information updating problems with the objective of minimizing the total production and inventory costs and established a mixed integer programming (MIP) model. To solve the problem of flexible process routes and frequent changes in workshop scheduling schemes in multiple varieties and small batch production modes, Sun et al [34] established a multi-process route scheduling optimization model with carbon emissions and cost as multiple objectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To solve this problem, they study six variants of the non-dominated sorting genetic algorithm-III (NSGA-III) and from the experimental results, it can be concluded that the NSGAIII-COE has significant advantages in solving the low carbon MO-FJSP. Sun et al [15] establish a multiprocess route scheduling optimization model with carbon emissions and cost as the multiobjective in order to solve the problems of flexible process route and workshop scheduling scheme changes frequently in the multivariety small batch production mode. The optimization results under single-target and multitarget conditions are contrasted and analyzed, to guide enterprises to choose a reasonable scheduling plan, improve the carbon efficiency of the production line, and save costs.…”
Section: Scheduling and Planning Issuesmentioning
confidence: 99%
“…In recent years, many scholars conducted research in the direction of production logistics process optimization, production logistics systems, and enabling technology applications. In production logistics process optimization, existing research focused on production logistics process optimization theories (e.g., lean logistics, green logistics), simulation modeling methods (e.g., Petri nets, heuristic algorithms) [17][18][19][20][21][22][23][24][25][26][27]. In terms of production logistics system research, existing studies focused on production equipment layout design, logistics scheduling, and process modeling (e.g., data flow diagram modeling, action diagram modeling) [14,28,29].…”
Section: Introductionmentioning
confidence: 99%